PENERAPAN MODEL PEMBELAJARAN KOPERATIF TIPE TEAM ASSISTED INDIVIDUALIZATION PADA MATERI KOORDINAT KARTESIUS DI SMP - Poligrentia, Agustina; R, Zubaidah; Ahmad BS, Dian (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractCooperative learning belongs to one of the learning models that is often and practically used by teachers. Cooperative learning is a strategy of learning that involves the participation of students in a small group to interact with each other. Cooperative learning expected learning outcomes of students can make for the better. This research aims to describe the effectiveness of TAI type of cooperative learning on cartesian coordinate matter in class VIII SMPN 21 Pontianak. Research method used is descriptive method. Research design used are direct observation technique and measurement technique. The results are teacher?s class management categorized very good, student?s learning activities categorized active and student?s output not reach the classical completeness. Based on that result, the conclusion is TAI type of cooperative learning on cartesian coordinate matter in class VIII SMPN 21 Pontianak not effective because there is one category that can?t be fulfilled. So, the implementation of TAI type of cooperative learning on cartesian coordinate matter in class VIII is not effective. Keywords:Team Assisted Individualization, Cartesian Coordinat, effective